Legal Protection of Kid Influencers from Child Exploitation - Jody Imam Rafsanjani (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Advances in information technology and improvements to internet network infrastructure make it easier for everyone to work and obtain information. There has been an adaptation of marketing techniques using influencer marketing, so the influencer profession is known. Unfortunately, to get marketing targets aimed at children, kid influencer services are a form of influencer marketing. Children are considered unable to make decisions about themselves. The roles of various parties are needed so that kid influencers can avoid acts of exploitation because the use or direction of children’s energy as kid influencers sacrifices children’s development both emotionally and physically. This article is to find out the fulfillment of children’s rights so that they can live, grow, develop, and participate optimally by human dignity and protection from violence and discrimination. This article uses a normative juridical approach, analyzed qualitatively. Based on literature study regarding legal protection, Indonesia ratified the United Nations Convention on the Rights of the Child with the Presidential Decree Number 36 of 1990 concerning Ratification of the Convention on the Rights of the Child; Amendment to the 1945 Constitution by including Article 28B Paragraph (2); and Law Number 23 of 2002 concerning Child Protection. It is hoped that all related parties will prioritize programs that protect children from exploitation in the implementation of all Child Protection instruments.